2020
DOI: 10.1055/s-0039-3402046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Graft Tensioning Effects in Anterior Cruciate Ligament Reconstruction between Hamstring and Bone–Patellar Tendon Bone Autografts

Abstract: This article investigates the clinical, functional, and radiographic outcomes in anterior cruciate ligament (ACL) reconstruction patients over 7 years to determine the effects of initial graft tension on outcomes when using patellar tendon (bone–tendon–bone [BTB]) and hamstring tendon (HS) autografts. Ninety patients, reconstructed with BTB or HS, were randomized using two initial graft tension protocols: (1) normal anteroposterior (AP) laxity (“low-tension”; n = 46) and (2) AP laxity overconstrained by 2 mm (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Further increase in the knee flexion angle led to an upsurge of laxity. Similar optimal graft fixation angles can be found in literature 107,108 , although a commonly used fixation angle is at 30°1 09,110 . Nonetheless, the optimal knee flexion angle during graft fixation is still a controversial topic amongst clinicians.…”
Section: Discussionsupporting
confidence: 72%
“…Further increase in the knee flexion angle led to an upsurge of laxity. Similar optimal graft fixation angles can be found in literature 107,108 , although a commonly used fixation angle is at 30°1 09,110 . Nonetheless, the optimal knee flexion angle during graft fixation is still a controversial topic amongst clinicians.…”
Section: Discussionsupporting
confidence: 72%
“…Although graft type was not randomized, a subsequent analysis was performed to explore the effects of graft type and tension on outcomes. 11 Several retrospective analyses (ancillary studies) were also performed using the Tension Trial database. 8,[12][13][14][15]17 3 | RESULTS…”
Section: Methodsmentioning
confidence: 99%
“…In the subsequent analysis evaluating the effects of graft type and tensioning on outcomes, 11 it was determined that patients reconstructed with HS autografts under the high-tension condition had better SF-36 scores (bodily pain, social functioning, and mental health scores; P < .014) than those HS patients reconstructed under low-tension, though there were no differences in any other outcome measures. Likewise, no differences in any outcome measures were found between the two graft tension conditions in those patients receiving BTB autografts.…”
Section: Randomized Controlled Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…Yasuda et al 37 compared sideto-side knee laxity at 2 years with initial graft tension at 20 N, 40 N, or 80 N in 70 patients and reported that 38 compared manual cyclical loading with the use of a tensioner at 1-year follow-up in 50 patients and reported no difference in laxity but better Lysholm score at short-term follow-up. Finally, DeFroda et al 39 also compared low-tension with high-tension (overconstrained by 2 mm) in 90 patients and reported on 72 patients at 7 years' follow-up using hamstrings or BPTB autografts. There were no differences in the BPTB group but statistically significant differences were reported favoring the high-tension group when the hamstrings grafts were used.…”
Section: Graft Tensioningmentioning
confidence: 99%